A novel and low-computation e-cash transfer system against blackmail for mobile communications. (19th May 2011) - Chen, Chin-Ling; Liu, Ming-He
Due to the rapid development of mobile communication technologies, several applications are proposed on the mobile devices. We present a novel and low-computation E-cash transfer system to prevent blackmail for mobile communications. Our proposed protocol is based on a session key with mutual authentication, a digital signature and a public key system. In our system, the problematic account designated by the criminal is able to be traced under the blackmail.